ANALISIS PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP TINGKAT PEMBIAYAAN BERMASALAH PADA BANK UMUM SYARIAH DI INDONESIA PERIODE TAHUN 2010-2014 - Auliani, Mia Maraya; Syaichu, Muhamad (Faculty of Economics and Business Diponegoro University, 2016)
Islamic banking at the moment is one of the important things in the economy of the country. Non Performing Financing became one ratio that is considered by the Islamic banking. NPF is an indicator that shows the risk of losses due to financing. The deterioration of the NPF ratio means Islamic banks have a high degree of financing problems. This study aimed to analyze the influence of internal and external factors of the NPF Islamic bank in Indonesia.The hypothesis testing use BOPO, CAR, FDR, SBIS, inflation and the exchange rate as an independent variable and the NPF ratio as the dependent variable. The population in this study are all Islamic banks in Indonesia. The sample used in this study is a quarterly financial report of Bank Syariah Mandiri, Bank Muamalat Indonesia, BRI Syariah, Bank Panin and Bank Syariah Bukopin Syariah 2010-2014 period and also the data of inflation and the exchange rate against the US dollar by using purposive sampling method. The data used is secondary data obtained from the financial statements can be downloaded from the official website of each bank and the official website of Bank Indoneisa. The analytical method used is multiple regression with a significance level of 5%.The result showing that in partial BOPO and SBIS influenced positive significant, while the CAR and inflation negative significant effect on the NPF Islamic banks. For FDR variables, inflation and exchange rate partially no effect on NPF. Simultaneously or together, variables BOPO, CAR, FDR, SBIS, inflation and exchange rate. Results of regression estimation show the predictive ability of the model 46,5%, while the remaining 53,5% influenced by other factors outside the model that has not been covered in this research.